(untitled) (The Peerian Journal, 2025)
This article studies the sources of creativity used by clothing designers to create new clothing collections, especially the role of material cultural objects such as architecture, architectural styles of different periods, and analyzes the design stages. Examples of practical developments developed by the author are presented. The results of the article are of scientific and practical importance